Fuzzy power flow : an AC model addressing correlated data - João Paulo Tomé Saraiva (2004)
This paper presents an enhanced version of an AC Fuzzy Power Flow model designed to integrate correlation data between nodal injections. The model gives the user the possibility to specify fuzzy numbers to represent the possible behavior of loads and generations and outputs fuzzy membership functions for voltage magnitudes and phases, active and reactive flows, losses and generations. The algorithm is organized in two basic steps. The first one corresponds to a linearized procedure while the second aims at introducing correlated data leading to a reduction of the width of the membership output functions. In a final section, we present results obtained with a case study based on a didactic power system to illustrate and highlight details of the proposed models.